1977
DOI: 10.2307/1589423
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Infectious Bursal Disease on the Development of Immunity to Eimeria tenella

Abstract: Specific-pathogen-free (SPF) chicks infected with infectious bursal disease (IBDV) virus at one day of age or midway (7 days) through a two-week immunization program for Eimeria tenella showed significantly less (P less than or equal to 0.05) protection against coccidal challenge as measured by lesion scores than chicks given IBDV after 14 days of coccidial immunization. The chicks showed complete protection to later coccidial challenge administered on Day 21. Bursae were markedly smaller from IBDV-infected ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Infection of specific pathogen free chicks with IBDV at either 1 or 7 days of age diminished protection against coccidiosis stimulated by administration of a low level (300 oocysts/bird/day) of Eimeria tenella over a 14-day period. Chickens infected with IBDV at either 1 or 7 days showed lower bursal mass and higher E. tenella lesion scores following challenge than non-IBD infected, E. tenella-vaccinated controls (Anderson et al, 1977). Cryptosporidiosis caused by Cryptosporidium baileyi is an emerging condition in areas with high poultry density.…”
Section: Immunosuppression and Interaction Of Ibdv With Other Pathogensmentioning
confidence: 98%
“…Infection of specific pathogen free chicks with IBDV at either 1 or 7 days of age diminished protection against coccidiosis stimulated by administration of a low level (300 oocysts/bird/day) of Eimeria tenella over a 14-day period. Chickens infected with IBDV at either 1 or 7 days showed lower bursal mass and higher E. tenella lesion scores following challenge than non-IBD infected, E. tenella-vaccinated controls (Anderson et al, 1977). Cryptosporidiosis caused by Cryptosporidium baileyi is an emerging condition in areas with high poultry density.…”
Section: Immunosuppression and Interaction Of Ibdv With Other Pathogensmentioning
confidence: 98%
“…It has been shown that immunosuppressive diseases or conditions may act in concert with Eimeria to produce a more severe coccidiosis. Marek's disease may interfere with development of immunity to coccidiosis (Rice and Reid, 1973), and infectious bursal disease may exacerbate coccidiosis (Anderson et al, 1977;McDougald et al, 1979).…”
Section: Coccidiosismentioning
confidence: 99%
“…The absence of clinical signs may be due to the degree of immunosuppression and/or an age resistance. IBD induced immunosuppression in broilers has been associated with a variety of clinical syndromes, such as chronic respiratory disease, coccidiosis (Anderson et al, 1977), inclusion body hepatitis (Fadly et al, 1976) and gangrenous dermatitis (Rosenberger et al, 1975). Such diseases are usually seen at 4 weeks of age, subsequent to immunosuppression caused by natural IBD virus infections, which occur when maternal antibodies wane (McFerran, 1989).…”
Section: Discussionmentioning
confidence: 99%